Patient-Reported Impact of Symptoms in Myotonic Dystrophy Type 2 (PRISM-2). (15th December 2015) - Heatwole, Chad; Johnson, Nicholas; Bode, Rita; Dekdebrun, Jeanne; Dilek, Nuran; Hilbert, James E.; Luebbe, Elizabeth; Martens, William; McDermott, Michael P.; Quinn, Christine; Rothrock, Nan; Thornton, Charles; et al.
Abstract : Objective: To determine the frequency and relative importance of the most life-affecting symptoms in myotonic dystrophy type 2 (DM2) and to identify the factors that have the strongest association with these symptoms. Methods: We conducted a cross-sectional study of adult patients with DM2 from a National Registry of DM2 Patients to assess the prevalence and relative importance of 310 symptoms and 21 symptomatic themes. Participant responses were compared by age categories, sex, educational attainment, employment status, and duration of symptoms. Results: The symptomatic themes with the highest prevalence in DM2 were the inability to do activities (94.4%), limitations with mobility or walking (89.2%), hip, thigh, or knee weakness (89.2%), fatigue (89.2%), and myotonia (82.6%). Participants identified the inability to do activities and fatigue as the symptomatic themes that have the greatest overall effect on their lives. Unemployment, a longer duration of symptoms, and less education were associated with a higher average prevalence of all symptomatic themes ( p < 0.01). Unemployment, a longer duration of symptoms, sex, and increased age were associated with a higher average effect of all symptomatic themes among patients with DM2 ( p < 0.01). Conclusions: The lives of patients with DM2 are affected by a variety of symptoms. These symptoms have different levels of significance and prevalence in this population and vary across DM2 subgroups in different demographic categories.